Chanting Tahreer and Compassion: People as Poetry - El Alaoui, Khadija (InTensions, 2011)
The contention of this essay is that the current Arab revolutions of the so-called Arab Spring must be seen in the context of broader resistance in the colonized Muslim world to global political modernity. This essay focuses especially on the constitutive role that poetry plays in resistance to colonialism and violence. After situating this general phenomenon of poetic resistance in a global context with reference to Abdelrahman Munif, Mahmoud Darwish and Langston Hughes, I examine the deep constitutive role of poetry in the revolutions of Tunisia and Egypt in 2010-11. I illuminate the beauty and meaningfulness of the poetry in the quotidian experience of those peoples making revolutions. Poetry runs through the lives, the feelings, and, importantly, the politics of their world, a world that includes pride in Arab values and solidarity against the ongoing violence and injustices of authoritarianism and occupation. My dwelling and meditation on poetry helps elaborate a vision of the new Arab revolts.